Business Opportunity : TuneWow / Abdul Azim Farihin Abdul Ghani - Abdul Ghani, Abdul Azim Farihin (2021)
The business that chosen for this assignment is being an agent of ToneWow. ToneWow is a branch of Digi Telco that produced a simcard with bombastic data and call plan. One reason of choosing Tonewow is the price is on the cheapest now that makes high demand of it. After we register in Tonewow with pay for the sim-card, automatically we can be a dealer. Because of that, the capital to begin this business just acquired RM12.50. Thus, online and offline marketing technique were applied.